FORMULATION OF VARIATIONS IN THE COMBINATION CONCENTRATIONS OF ROBUSTA COFFEE (Coffea canephora) POWDER AND TURMERIC RHIZOME EXTRACT (Curcuma longa L.) ON THE QUALITY OF BODY SCRUB PREPARATIONS - Sumiyati; Rosanti, Afi Sania; Dwiningrum, Riza; Safutri, Wina (LPPM Universitas Dhyana Pura, 2025)
Body scrub is a skincare product used to exfoliate dead skin cells and accelerate skin regeneration. Natural ingredients such as robusta coffee powder (Coffea canephora), which contains caffeine, act as a natural exfoliant, while turmeric rhizome extract (Curcuma longa L.), which contains curcuminoids, functions as an antioxidant and skin brightener. This study aimed to formulate a body scrub using varying concentrations of robusta coffee powder and turmeric extract, and to evaluate its physical properties, stability, and consumer preference. An experimental method was used with five formulations: F1 (10% coffee), F2 (10% turmeric), F3 (7%:3%), F4 (8%:2%), and F5 (9%:1%). Evaluations included organoleptic testing, homogeneity, pH, spreadability, adhesion, cream type, viscosity, stability, and hedonic testing. Results showed that all formulations met the criteria for good physical quality. Based on hedonic tests, F1 was the most preferred in terms of color, while F4 was most favored for aroma and texture, making it the best formulation with no significant difference (p>0.05). This study supports the development of natural body scrubs using local ingredients that are safe and effective.